Pengabdian Kepada Masyarakat Melalui Kuliah Kerja Nyata (KKN) di Desa Mangunjaya Kabupaten Bekasi - Elia Rossa; Muhammad Esa Septian; Lissa Rahmawati; Fathiyah Alifah Fitriyani; Cahaya Zulfah; Putri Afrilia Nurrochmah; Herlina Yuliyanti; Dina Erliana; Nanda Suci Handayani Umagap; Ajeng Putri Wahyuningtyas (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2024)
The Real Work Lecture is a community service program that aims to practice the Tri Dharma of Higher Education. One way students can help overcome problems in the community is by devoting themselves to the community through Community Service Lectures (KKN). The purpose of this study is to learn how Real Work Lectures contribute to increasing environmental awareness and providing education to children in Mangunjaya Village, Bekasi Regency. This study uses an observation method and this study contains a description of the planning process and implementation of Real Work Lecture activities. The subject of the implementation of the Community Real Work Lecture in Mangunjaya Village RT 006/RW 003. The results of the study show that environmental awareness in Mangunjaya Village has increased significantly as a result of the Real Work Lecture, even though there are some conditions that are less than ideal, the community is still happy to participate in the KKN program designed by students, there are no obstacles in the preparation, implementation and evaluation of programs that are planned and held according to the previous plan such as reading and writing, counting, playing, saving can be carried out well. In this activity, the manufacture and installation of directional signs as well as appeal banners are carried out through cooperation, coordination and participation. The community is beginning to realize how important it is to keep the environment clean and healthy. Children also better understand the importance of saving and increasing their knowledge through educational learning provided by Real Work Lecture students. It is hoped that this program can provide insight to the community about the potential and development of the village.